All-inkjet-printed flexible piezoelectric generator made of solvent evaporation assisted BaTiO3 hybrid material. (November 2017) - Lim, Jongwoo; Jung, Hyunsung; Baek, Changyeon; Hwang, Geon-Tae; Ryu, Jungho; Yoon, Daeho; Yoo, Jibeom; Park, Kwi-Il; Kim, Jong Hee
Abstract: Attractive approaches based on flexible piezoelectric energy harvesting technology that convert ambient mechanical energies into electrical energy have attracted attention in response to recent progress in the field of flexible electronics technology. Although the harvesters on plastic substrates has shown the feasibility of the piezoelectric energy generation from the repetitive and tiny bending deformations, the complicated fabrication process and size limitations hinder the commercialization of piezoelectric self-powered technology. In this study, all-inkjet-printed flexible piezoelectric energy harvester based on a BaTiO3 hybrid film is demonstrated by adopting only a simple and facile inkjet-printing process. Flexible/large-area piezoelectric hybrid film and Ag electrode layers are printed onto a flexible substrate by only non-contact inkjet process without high temperature annealing and complicated transfer processes. All-inkjet-printed energy harvester converts the periodically mechanical deformations into an open-circuit voltage (Voc ) of ~ 7 V, a short-circuit current (Isc ) of 2.5 μA (corresponding to a current density of 0.21 μA·cm −2 ), and an effective output power of around 5 μW (corresponding to a power density of 0.42 μW·cm −2 ). This novel approach provides an innovative platform for self-powered system and inorganic-based flexible electronics. Graphical abstract: All-inkjet-printed flexible energy harvester made of BaTiO3 - resin hybrid film has been demonstrated by introducing a simple, facial, and scalable inkjet-printing process. Flexible piezoelectric BaTiO3 - resin hybrid film and conductive layers are printed onto a plastic substrate by only non-contact inkjet process without high temperature annealing and complicated transfer processes. Highlights: All-inkjet-printed f-PEH was fabricated by using a practical inkjet-printing process. Piezoelectric BaTiO3 nanoparticles and resin were inkjet-printed onto a plastic substrate. The fabricated f-PEH generates the output voltage of ~ 7 V and current of 2.5 μA. The flexible energy harvester showed mechanically stable under periodic bendings.